Dynamic mechanical behavior, damage mode and mechanism of multi-scale high energy insensitive particulate reinforced composites of a new type of anti-missile sandwich wall structure. (October 2019) - Cai, Xuanming; Zhang, Wei; Gao, Yubo; Fan, Zhiqiang
Highlights: The resulting dynamic stress-strain curves of the multi-scale high energy insensitive particulate reinforced composites are obtained at various high strain rates. A dynamic constitutive equation was established to describe dynamic mechanical behavior of the multi-scale high energy insensitive particulate reinforced composites within the density, strain and strain rates. With the increase of impact loading pressure, meso-damage modes such as shear debonding, surface fracture, breakage and melting of particles gradually appear. Abstract: Multi-scale high energy insensitive particle reinforced composites (MSHEIPRC) are the most important part of the anti-missile sandwich wall structure. Its dynamic mechanical behavior and damage mode will directly affect the success of anti-missile capability. In this paper, based on a modified Split Hopkinson Pressure Bar (SHPB) experimental technique and the design of triaxial impact loading test device, combining with theoretical study and meso analysis, the dynamic mechanical response under high strain rates and damage characteristics of MSHEIPRC under high overload were carried out. The results show that the dynamic stress-strain curves of MSHEIPRC are highly non-linear and have obvious strain rate effect and density effect. Compared with the experimental results, the modified constitutive model can accurately describe its dynamic mechanical behavior at high strain rates. Based on the energy model and related parameters, the bond strength between the surface of crystal particles and the binder is calculated to be about 0.6 MPa. Therefore, the shear debonding damage mode between the surface of crystal particles and the binder is first found at the stage of small impact loading. The critical fracture strength of cracks with different sizes is calculated by Griffith method. With the increase of impact loading pressure, the fracture phenomenon gradually appeared on the surface of crystal particles, which was basically consistent with the theory model. Continuing to increase the impact loading pressure, sufficient shock wave energy forces crystal particles to produce transgranular fracture, which leads to crystal particles breaking.